Could piracetam potentiate behavioural effects of psychostimulants? - Slais, Karel; Machalova, Alena; Landa, Leos; Vrskova, Dagmar; Sulcova, Alexandra (Medical hypotheses, 2012)
Press and internet reports mention abuse of nootropic drug piracetam (PIR) in combination with psychostimulants methamphetamine (MET) or 4-methylenedioxymethamphetamine (MDMA). These combinations are believed to produce more profound desirable effects, while decreasing hangover. However, there is a lack of valid experimental studies on such drug-drug interactions in the scientific literature available. Our hypothesis proposes that a functional interaction exists between PIR and amphetamine psychostimulants (MET and MDMA) which can potentiate psychostimulant behavioural effects. Our hypothesis is supported by the results of our pilot experiment testing acute effects of drugs given to mice intraperitoneally (Vehicle, n=12; MET 2.5mg/kg, n=10; MDMA 2.5mg/kg, n=11; PIR 300 mg/kg, n=12; PIR+MET, n=12; PIR+MDMA, n=11) in the Open Field Test (Actitrack, Panlab, Spain). PIR given alone caused no significant changes in mouse locomotor/exploratory behaviour, whereas the same dose combined with either MET or MDMA significantly enhanced their stimulatory effects. Different possible neurobiological mechanism underlying drug-drug interaction of PIR with MET or MDMA are discussed, as modulation of dopaminergic, glutamatergic or cholinergic brain systems. However, the interaction with membrane phospholipids seems as the most plausible mechanism explaining PIR action on activities of neurotransmitter systems. Despite that our behavioural experiment cannot serve for explanation of the pharmacological mechanisms of these functional interactions, it shows that PIR effects can increase behavioural stimulation of amphetamine drugs. Thus, the reported combining of PIR with MET or MDMA by human abusers is not perhaps a coincidental phenomenon and may be based on existing PIR potential to intensify acute psychostimulant effects of these drugs of abuse.
Keywords: Drug Synergism; kombinovaná farmakoterapie; Drug Therapy, Combination; Mice; zvířata; piracetam; Behavior, Animal; synergismus léků; neuroprotektivní látky; Neuroprotective Agents; chování zvířat; Piracetam; Amphetamines; amfetaminy; myši; Dose-Response Relationship, Drug; Animals; vztah mezi dávkou a účinkem léčiva; stimulanty centrálního nervového systému; Central Nervous System Stimulants